Status of livestock research and Development in the highlands of Ethiopia - Sileshi, Z.; Tsegahun, A.; Yami, A.; Tegegne, Azage (International Maize and Wheat Improvement Center, 2001)
In Ethiopia, the agricultural sector is a cornerstone of the economic and social life. The sector employs 80-85 per cent of the population and contributes 40 per cent to total GDP. Smallholder farmers dominate the agricultural sector. The highlands hold about 95 per cent of the cropped area and support two-thirds of the livestock population. It is estimated that the highland areas contain 75-80 per cent each of the national cattle and sheep flock and about 30 per cent of the national goat flock. In general, three production systems can be recognised; extensive pastoralism in arid and semiarid rangelands, integration of animals with cropping in rain-fed and irrigated areas and systems associated with perennial tree crops. The last two systems are significant with respect to integration of crops and livestock. The parastatal and private-based intensive livestock production systems are recent Developments, which only account for about 5 percent of the livestock population. A very few private intra- and periurban dairy and fattening operations are being undertaken around major cities/towns. Mixed crop-livestock farmers with varying levels of intensification own almost all the livestock in the highlands. Determinant factors for evolution of crop-livestock systems and components of integration of the systems are discussed in the paper. The livestock sector in Ethiopia has been constrained due to many factors. In fact, there is no systematic assessment of constraints to livestock production of the different farming systems and zones. Lack of understanding of the farming systems, constraints and prospects of possible interventions in line with the socioeconomic scenarios of the farmers constitutes by itself the fundamental problem to the sub-sector. Seasonal fluctuations of nutrient supply, both in quality and quantity, are the main nutritional constraint. The livestock sector is also challenged by a plethora of diseases. The paper highlights research and Development efforts made in small ruminant, poultry and cattle (dairy and beef) production. Past research and Development efforts were limited as compared to the potential of the animal sector to the livelihood of the Ethiopian farmers and to the national economy at large. Though considerable technologies were generated by the national research system, the adoption of these by smallholder farmers have been very limited. There are many reasons for this scenario. Some of the major factors are lack of designated institutions that multiply these technologies; inadequate system of supporting institutions (micro financing, cooperatives, etc) to access technologies by small holder farmers, and the lack of an integrated systems approach in designing improvements to farming systems. The current challenge of sustaining agricultural productivity to meet the exigencies of the next century is complex and multifaceted. Accelerated growth rate of agriculture depends heavily on the availability of improved technology, stimulated by institutional and policy changes. The change has to be built on understanding of the system right from the grass root level with a firm base on better management of human and natural resources. The incompetence of research in providing tangible improvements in the past warrants evaluation of the research direction, methods, and priorities. Recently, national agricultural research has been structured by establishing the Ethiopian Agricultural Research Organization (Ethiopian Agricultural Research Organization). The primary objectives of Ethiopian Agricultural Research Organization are to promote, guide and coordinate agricultural research in the country. National livestock research strategy is designed on a demand-driven and problem-oriented approach, with considerable resources invested in stakeholders problem assessment. Short and long term research are formulated. Research focus is given to smallholders farming systems, improvement of nutrition and testing available technologies. The paper highlights short-term research themes in the area of small ruminant, dairy, beef and poultry production.